Low-coverage vaccination strategies for the conservation of endangered species. - Haydon, D; Randall, D; Matthews, L; Knobel, D; Tallents, L; Gravenor, M; Williams, S; Pollinger, J; Cleaveland, S; Woolhouse, M; Sillero-Zubiri, C; Marino, J; et al. (2006)
The conventional objective of vaccination programmes is to eliminate infection by reducing the reproduction number of an infectious agent to less than one, which generally requires vaccination of the majority of individuals. In populations of endangered wildlife, the intervention required to deliver such coverage can be undesirable and impractical; however, endangered populations are increasingly threatened by outbreaks of infectious disease for which effective vaccines exist. As an alternative, wildlife epidemiologists could adopt a vaccination strategy that protects a population from the consequences of only the largest outbreaks of disease. Here we provide a successful example of this strategy in the Ethiopian wolf, the world's rarest canid, which persists in small subpopulations threatened by repeated outbreaks of rabies introduced by domestic dogs. On the basis of data from past outbreaks, we propose an approach that controls the spread of disease through habitat corridors between subpopulations and that requires only low vaccination coverage. This approach reduces the extent of rabies outbreaks and should significantly enhance the long-term persistence of the population. Our study shows that vaccination used to enhance metapopulation persistence through elimination of the largest outbreaks of disease requires lower coverage than the conventional objective of reducing the reproduction number of an infectious agent to less than one.